The Implementation of Complete Systematic Land Registration Program - Winanda, Winanda (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
Proof of Ownership Land rights are important in the midst of the increasing need for land, registering land parcels so that there is legal certainty in the land parcels of the people who own them in order to avoid disputes and legal issues related to the legal status of the land parcels under their control. For the State, the Complete Systematic Land Registration Program makes it easier for the government to organize cities. This study aims to find out how the implementation of the Complete Systematic Land Registration Program in the City of Cirebon and to determine the role of the Village/Village in Supporting the Implementation of the Land Registration Program in the City of Cirebon. The approach used in this study uses a sociological juridical approach, with a research specification that is analytical descriptive. The data used are primary and secondary data, where primary data is obtained by means of interviews and secondary data by way of literature study. The data analyzed was carried out qualitatively. Based on the research, it was concluded that the Implementation of the Complete Systematic Land Registration Program in the City of Cirebon went according to the stages in its implementation, starting from the planning and preparation, counseling and outreach stages starting from the Village/Village level as the smallest government that directly deals with the community and the factors that impede the Village/Village Government to support the smooth running of government programs. Conclusions and suggestions as a solution to the problem are sanctions imposed on each related agency that does not support programs that aim to prosper the community.Keywords: Implementation; Land; Ownership.